Analisis Semiotika dalam Tradisi Semoyo Putu di Desa Alaskobong Kecamatan Sempuh Kabupaten Banyuwangi - Fitakhu Khoirul Ilmiah; Nuril Huda; Haerussaleh Haerussaleh (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Tradition is a habit that is passed down from generation to generation in a group, the semoyo putu tradition is a tradition that exists in the Banyuwangi area, this tradition is a kind of ruwatan for families. This study aims to explore the markers and signifieds contained in the semoyo putu tradition. This study uses a descriptive qualitative approach, data was collected through observation, audiovisual documentation, and in-depth interviews. The findings in the semoyo putu tradition show markers and signifieds, the findings in this study such as sprouted coconuts, jenang lemu, moringa vegetables, pitung tawar, white cloth, setaman flower water, and tumpeng. The results of this study indicate that each finding has a meaning to the values ​​upheld by the community, sprouted coconuts as a symbol of hope, jenang lemu reflects the hope for longevity, moringa vegetables symbolize health, pitung tawar as a ward off disaster, white cloth as a symbol of sincerity, setaman flower water depicts the fragrance of life, and tumpeng as a form of gratitude. This finding confirms that the relationship between signifiers and signifieds is arbitrary and socially constructed in the context of local culture.